Untersuchung potenzieller Wellenformen zur Broadcast-Datenübertragung mittels Pulsradar - Michael Allinger (2022)
“Radar Communication”, short „RadComm“, is a concept of a joint radar and wireless system. Todays research is focusing on short-range radars used in the automotive industry. The technology used there differs from the technology used in sea- and air-based radars, where typically pulse-doppler-radars are installed. Therefor this thesis is investigating the suitability of RadComm as a concept for pulse-doppler-radars. For radar technology is no special field in “Medientechnik” it had to be researched in advance. Based on this research this thesis contains a short overview over radar technology and derived requirements for data transmission. Additionally, it contains a chapter to “fountain codes” found during research, their complexity in practical use and a simulation to check the performance of fountain codes. The conclusion includes a simulation of a sampled bit-sequence to check for radar compatibility.
Keywords: RadComm; Radartechnik; Fountain Codes; Puls-Radar; MATLAB